"Women in African Women's Writings: A Study of Novels by Buchi Emecheta and Tsitsi Dangarembga." - (:unkn) unknown (My University, 2017)
Abstract:Women, throughout the world, are under the sway of various scourges that range from gender-based discrimination, male chauvinism to physical violence. In the light of this, one needs to ask the role scholars and intellectuals play to change this reality. It is from this perspective we should understand the ostracism of women writers from the literary field. However, thanks to their commitment, some of them use the feminist literary tradition as a writing strategy designed to dismantle the myths that hamper their emancipation as individuals.The two women writers concerned in this study, Buchi Emecheta and Tsitsi Dangarembga, dig deep in mainstream feminist literary criticism in their novels. In that respect, they base their work on their own African cultural context and respective countries to investigate the social aspects of women’s subjugation, and mount a protest against it. Through female characterization, they put under the critical spotlight patriarchy with encroaching cultures and colonization that compromise women’s promotion. This illustrates their commitment to women’s fight for social justice, with greater scope and in-depth analysis, regardless of gender-based obstacles. The novels studied here are discursively intertwined, as the two women writers build their female protagonists’ own stories around the triptych that rebounds in women’s writings, gender, race and class, discriminatory categories that impede their growth from childhood to womanhood. Their entrapment is unquestioned because tradition and colonization collude to subjugate them. Since women are victims of prejudices, the female characters Emecheta and Dangarembga depict in their works design survival strategies to outsmart social injustice for a better world. Such strategies give some measure of optimism to their fiction, which can be labeled as apprenticeship and/or development novels. Thus, their ingenuity to adapt mainstreaming feminist tradition to the
Keywords: African Research